2008
DOI: 10.1603/0022-2585(2008)45[1108:fgrfri]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

<I>Francisella</I> Genes Required for Replication in Mosquito Cells

Abstract: Francisella tularensis, a potential bioterrorism agent, is transmitted by arthropod vectors and causes tularemia in many mammals, including humans. Francisella novicida causes disease with similar pathology in mice. We show that F. novicida invades hemocyte-like cells of the SualB cell line derived from Anopheles gambiae and replicates vigorously within these cells. We used transposon knockouts of single genes of F. novicida to show that bacterial growth within these insect cells is dependent on virulence fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…For mutants, such as iglG and iglI, contradicting results exist (dark gray boxes). For strains which carry duplications of the FPI genes, the stated phenotypes and references refer to mutants that contain deletions in both copies of the FPI gene . Supporting data from: 1 Schmerk et al (2009a), 2 Ludu et al (2008), 3 Åhlund et al (2010), 4 Kraemer et al (2009), 5 Barker et al, (2009), 6 Rodriguez (2010), 7 Asare and Abu Kwaik (2010), 8 Brotcke et al (2006), 9 Tempel et al (2006), 10 Golovliov et al, (2003a), 11 Lauriano et al, (2004), 12 Bröms et al (2009), 13 de Bruin et al (2007), 14 Santic et al (2005b), 15 Bönquist et al (2008), 16 Lindgren et al (2004), 17 Bröms et al (unpublished), 18 Weiss et al (2007), 19 Gray et al (2002), 20 Read et al (2008), 21 Vonkavaara et al (2008), 22 Lai et al (2004) .…”
Section: The Francisella Pathogenicity Islandmentioning
confidence: 99%
See 1 more Smart Citation
“…For mutants, such as iglG and iglI, contradicting results exist (dark gray boxes). For strains which carry duplications of the FPI genes, the stated phenotypes and references refer to mutants that contain deletions in both copies of the FPI gene . Supporting data from: 1 Schmerk et al (2009a), 2 Ludu et al (2008), 3 Åhlund et al (2010), 4 Kraemer et al (2009), 5 Barker et al, (2009), 6 Rodriguez (2010), 7 Asare and Abu Kwaik (2010), 8 Brotcke et al (2006), 9 Tempel et al (2006), 10 Golovliov et al, (2003a), 11 Lauriano et al, (2004), 12 Bröms et al (2009), 13 de Bruin et al (2007), 14 Santic et al (2005b), 15 Bönquist et al (2008), 16 Lindgren et al (2004), 17 Bröms et al (unpublished), 18 Weiss et al (2007), 19 Gray et al (2002), 20 Read et al (2008), 21 Vonkavaara et al (2008), 22 Lai et al (2004) .…”
Section: The Francisella Pathogenicity Islandmentioning
confidence: 99%
“…Both have been shown to be essential for the ability of F. tularensis to modulate the biogenesis of the phagosome to avoid lysosomal fusion (Santic et al, 2005b; Bönquist et al, 2008), to escape into the host cytosol (Lindgren et al, 2004; Santic et al, 2005b), and to induce apoptosis of J774 cells (Lai et al, 2004; Table 3). Consequently, mglA and iglC mutations diminish intracellular survival and growth in many different macrophage-like cell lines (Gray et al, 2002; Golovliov et al, 2003a; Lauriano et al, 2003; Lindgren et al, 2004; Santic et al, 2005b), as well as ameba (Lauriano et al, 2004) and insect cells (Read et al, 2008; Vonkavaara et al, 2008; Santic et al, 2009; Table 3). To date, most of the genes located in the FPI, such as iglA , iglB , iglC , iglD , iglI , iglG, pdpA , pdpB , and pdpD , have been demonstrated to be required either for intramacrophage growth and/or virulence of at least one subspecies (Golovliov et al, 2003b; Lai et al, 2004; Nano et al, 2004; Tempel et al, 2006; de Bruin et al, 2007; Santic et al, 2007; Weiss et al, 2007; Bönquist et al, 2008; Chong et al, 2008; Ludu et al, 2008; Bröms et al, 2009; Schmerk et al, 2009b; Bröms et al, unpublished; Table 3).…”
Section: The Francisella Pathogenicity Islandmentioning
confidence: 99%
“…have a type VI secretion system, which plays an important role in promoting growth within arthropods; this secretion system was previously reported to be critical for intracellular growth in a mosquito cell line (Read et al, 2008). In addition, we previously showed that the type VI secretion system was directly involved in proliferation of Francisella within silkworms (Saha et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…made their own F. novicida transposon mutant library and screened it in mice following intraperitoneal infection and did not identify grx mutants ( Weiss et al., 2007 ). Similarly, using Gallagher et al's F. novicida transposon mutants in SualB cells (hemocyte-like cells from the mosquito Anopheles gambiae ) no grx mutants were identified ( Read et al., 2008 ). Perhaps these differences reflect polar downstream effects of the mutations or reflect differences in the host cell lines (insect versus mammalian).…”
Section: Introductionmentioning
confidence: 99%